Reorganization Energy upon Controlled Intermolecular Charge-Transfer Reactions in Monolithically Integrated Nanodevices - Merces, Leandro; Candiotto, Graziâni; Ferro, Letícia Mariê Minatogau; de Barros, Anerise; Batista, Carlos Vinícius Santos [UNESP]; Nawaz, Ali; Riul, Antonio; Capaz, Rodrigo B.; Bufon, Carlos César Bof [UNESP] (Wiley, 2021)
Intermolecular electron-transfer reactions are key processes in physics, chemistry, and biology. The electron-transfer rates depend primarily on the system reorganization energy, that is, the energetic cost to rearrange each reactant and its surrounding environment when a charge is transferred. Despite the evident impact of electron-transfer reactions on charge-carrier hopping, well-controlled electronic transport measurements using monolithically integrated electrochemical devices have not successfully measured the reorganization energies to this date. Here, it is shown that self-rolling nanomembrane devices with strain-engineered mechanical properties, on-a-chip monolithic integration, and multi-environment operation features can overcome this challenge. The ongoing advances in nanomembrane-origami technology allow to manufacture the nCap, a nanocapacitor platform, to perform molecular-level charge transport characterization. Thereby, employing nCap, the copper-phthalocyanine (CuPc) reorganization energy is probed, ≈0.93 eV, from temperature-dependent measurements of CuPc nanometer-thick films. Supporting the experimental findings, density functional theory calculations provide the atomistic picture of the measured CuPc charge-transfer reaction. The experimental strategy demonstrated here is a consistent route towards determining the reorganization energy of a system formed by molecules monolithically integrated into electrochemical nanodevices.
Keywords: density functional; electrochemical; electron transfer; hopping; Marcus; nanogap; nanomembrane origami